Political Branding Rano Karno Dalam Pilkada Jakarta 2024 Sebagai “Si Doel” Melalui Akun Instagram @si.doel - Cahyaningrum, Zafira Rizqi; Zamzamy, Ahmad (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
Rano Karno is running for the regional head election again. This time he is running for Deputy Governor of Jakarta accompanying Pramono Anung. He used his popularity as Si Doel as political branding in the 2024 Jakarta Regional Election campaign. This study highlights how Rano uses a fictional character with a cultural background for his political branding. Rano’s Instagram account @si.rano is used as a platform to build his branding as Si Doel during the 2024 Jakarta Regional Election campaign. A total of 23 uploads were analyzed using content analysis techniques which were then categorized and dissected based on Peter Montoya's theory of 8 laws of personal branding. The results of this study show how a fictional character can be used for political branding. Rano built his image as Si Doel through the @si.rano account well. Based on the 8 laws of personal branding, he focuses on branding that contains aspects of his specialization in Betawi art and culture and his visibility as Si Doel. This gives a fresh air that can be adapted for politicians in the future